A Decade of Thunderstorm Patterns: A Comparative Study of Iraq and Russia - Al-khulaifawi, Imad Abdulridha; Ruvimovich, Ioshpa Alexander (Iraqi Journal of Science, 2025)
This study analyzes thunderstorm activity based on archived data from daily meteorological observations over 10 years at three meteorological stations in Iraq (Khanaqin, Baghdad Airport, and Basra Airport) and at two meteorological stations in Russia (Rostov-on-Don and Taganrog). The analysis showed that the greatest frequency of thunderstorms occurred in March and April, 55% of them were in the northern mountainous part of Iraq. Analysis of the fronts for six months per year and for a 10-year period showed 75 baroclinic and 77 barotropic cases for Khanaqin station, 45 baroclinic and 36 barotropic cases for Baghdad Airport station, and 33 baroclinic and 22 barotropic cases for Basra Airport station. But in Russia (Rostov-on-Don and Taganrog), the results showed that the greatest frequency of thunderstorms occurred in June and July, 53.58% of them are in Taganrog due to the warming from the sea and the arrival of a cold mass from the north (from the polar). Analysis for six months per year and for a period of 10 years showed that there were 76 baroclinic and 60 barotropic cases in Rostov-on-Don and 80 baroclinic and 76 barotropic cases in Taganrog. The aim of the study is to analyze thunderstorms and the reasons for their recurrence in some stations more than others, and to predict the storm to reduce or avoid the damage caused by thunderstorms.